Impact of an exercise intervention on methamphetamine use outcomes post-residential treatment care. (1st November 2015) - Rawson, Richard A.; Chudzynski, Joy; Mooney, Larissa; Gonzales, Rachel; Ang, Alfonso; Dickerson, Daniel; Penate, Jose; Salem, Bilal A.; Dolezal, Brett; Cooper, Christopher B.
Highlights: We examine the effect of exercise on posttreatment methamphetamine (MA) use. We study 8 weeks of exercise vs. health education in residential treatment patients. Lower severity MA-dependent patients who exercised used MA fewer days posttreatment. Higher severity MA users did not show these results. Findings support exercise as a treatment component for lower severity MA users. Abstract: Background: We examined the efficacy of an 8-week exercise intervention on posttreatment methamphetamine (MA) use among MA-dependent individuals following residential treatment. Methods: 135 individuals newly enrolled in treatment were randomly assigned to a structured 8-week exercise intervention or health education control group. Approximately 1 week after completion of the intervention, participants were discharged to the community. Interview data and urine samples were collected at 1-, 3-, and 6-months post-residential care. Of the sample, 54.8% were classified as higher severity users (using MA more than 18 days in the month before admission) and 45.2% as lower severity users (using MA for up to 18 days in the month before admission). Group differences in MA use outcomes were examined over the 3 timepoints using mixed-multivariate modeling. Results: While fewer exercise participants returned to MA use compared to education participants at 1-, 3- and 6-months post-discharge, differences were not statistically significant. A significant interaction for self-reported MA use and MA urine drug test results by condition and MA severity was found: lower severity users in the exercise group reported using MA significantly fewer days at the three post-discharge timepoints than lower severity users in the education group. Lower severity users in the exercise group also had a lower percentage of positive urine results at the three timepoints than lower severity users in the education group. These relationships were not present in the comparison of the higher severity conditions. Conclusion: Results support the value of exercise as a treatment component for individuals using MA 18 or fewer days/month.